1980
DOI: 10.1002/j.1551-8833.1980.tb04598.x
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of microorganisms in water main encrustations

Abstract: Colonization of microorganisms and resultant high bacterial populations often occur on or within protective encrustations or tubercules inside a distribution system. Formation of these encrustations is affected by a variety of physical, chemical, and biological activities within the pipes, which can be examined in situ by scanning electron microscopy (SEM). SEM photographs demonstrate graphically the survival of microorganisms in the distribution system and their possible role in tubercle formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0
1

Year Published

1980
1980
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 2 publications
1
32
0
1
Order By: Relevance
“…The ultrastructural features of the surface matrixes were very similar to those reported for other municipal distribution systems (1,8,14,18). Moreover, the occurrence of bacteria within surface encrustations of Springfield's biofilms is consistent with prior findings (1,9,13,19). Unique to the present study is the presence of fungal spores as a major component of surface biofilms and encrustations.…”
supporting
confidence: 86%
“…The ultrastructural features of the surface matrixes were very similar to those reported for other municipal distribution systems (1,8,14,18). Moreover, the occurrence of bacteria within surface encrustations of Springfield's biofilms is consistent with prior findings (1,9,13,19). Unique to the present study is the presence of fungal spores as a major component of surface biofilms and encrustations.…”
supporting
confidence: 86%
“…Diatoms have been observed in waters from urban distribution networks (Allen et al, 1980), and other algae and cyanobacteria have been also reported (Ribas & Oliver, 1970). Some odours and tastes in drinking water have been associated with the presence of algae as well as actinomycetes and yeasts (Bower & Crowe 1988;Lee et al, 1980;Rizet et al, 1984).…”
Section: Introductionmentioning
confidence: 94%
“…However, these treatments may not prevent heterotrophic bacteria occurring in drinking water (van der Kooij, 1977), and it is possible that this could also be the case with algae. Evidence is available to show the development of biofilms containing algae and bacteria on most pipe surfaces (Allen et al, 1980;Le Chevallier et al, 1987). This biofilm might serve as an inoculum for microorganisms in tap waters.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, such tubercles or nodes do not necessarily reflect an inadequate water or disinfectant treatment, but the result of a constant adaptation of bacterial populations to environmental changes [3,4].…”
Section: Introductionmentioning
confidence: 99%